Traumatic dislocations of the hip in children About 11 cases and literature review - Mohammed Lahfaoui (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Traumatic dislocation of the hip in childhood is rare. Several small series of this condition have been published. The objective of this study was to evaluate the outcome of treatment of traumatic posterior hip dislocation in children. Data from 11 children (11 hips) with traumatic hip dislocation, collected in 2 centres (2 countries), from January 2010 to January 2019 were analysed. The clinical assessment focused on symptoms and physical findings. X-rays identified the type of hip dislocation. Hip dislocations were classified according to Thompson and Epstein. Reduction was performed using three techniques: technique 1, closed reduction. Technique 2, release of the long adductor muscle, lengthening of the psoas tendon, and placement of a Kirschner wire through the femoral head into the acetabulum. Technique 3, open reduction after hip arthrolysis. X-rays were then used to determine whether the hip is concentric and to check for any other injuries that may have occurred after manipulation. There were 3 girls (27.3%) and 8 boys (72.7%) in this study. All had Type I posterior hip dislocation. Patients at the time of diagnosis were 3 years, 2 months to 9 years, 10 months old. Reduction was performed using technique 1 in 8 patients, technique 2 in 2, and technique 3 in 1 child. We obtained excellent results in four hips (36.4%), good results in three hips (36.4%), satisfactory results in two hips (18.2%), and poor results in two hips (9.1%). There was avascular necrosis in two hips (18.2%), coxa magna in one patient (9.1%), limb inequality of 2 cm in one patient (9.1%), and lameness in one patient (9.1%). Hip scores averaged 82.4 points (range 62-100). Children with traumatic hip dislocation should be reduced as much as possible. If the interval between dislocation and reduction exceeds 3 weeks, we suggest technique 2. This simple and safe method leads to a marked improvement in hip function and prevents further complications.